PENGARUH KUALITAS PRODUK TERHADAP VOLUME PENJUALAN PADA PENGUSAHA SATE MARANGGI DI PURWAKARTA - Diki Rahmatulah, - (2009)
This Research is meant to know how a company earn to growing up quality of product which on the market to buyer candidate, because basically the quality of product is matter which basis for improve sale volume. Activity executed by company to improve volume of sale is improved the quality of product. Basically the quality of efficient and effective product will yield impact which are positive to buyer candidate. And so do conducted by Entrepreneur Broil Maranggi in Purwakarta, improved the quality of product is most precise medium for Entrepreneur Broil Maranggi in Purwakarta to bring influence which are positive to sale volume which wanted. In activity of this research is used by descriptive method of analysis, that is a[n method used to check problems which is on a period of now with problems which is actual. Technique which utilized in this method is approach of analysis of korelasional by analysis quality of product is entrepreneur, and analysis the influence of to got by sale volume is Entrepreneur Broil Maranggi in Purwakarta. Result of from this research is variable is quality of product as variable of X have positive contribution to variable of Y that is sale volume. Of the research result express that product quality have an effect on to sale volume at Entrepreneur Broil Maranggi in Purwakarta. Thereby if company improve the quality of product hence Entrepreneur a will succeed as according to what is planned. So that especial target of company to get advantage of sales revenue of terealisasi.